PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP HASIL BELAJAR IPS SISWA KELAS 4 SEKOLAH DASAR - Marsita Dewi Widyaningrum; Nyoto Harjono (Universitas Pakuan, 2019)
THE INFLUENCE OF JIGSAW LEARNING MODEL IN INCREASING THE LEARNING OUTCOME SOCIAL STUDIES (IPS) SUBJECT FOR STUDENTS IN CLASS 4 ELEMENTARY SCHOOL. The purpose of this research was to re-analyze the use of cooperative learning type jigsaw model in increasing the learning outcome in social studies subject. The research method was meta-analysis. The research began with formulating research problems, then trancing relevant research result to be analyzed. The data was collected by browsing article, electronic journals, and essay using “learning outcomes”, “jigsaw model”, and “Social Studies of Primary Education”. The searching result showed that there were 12 articles, electronic journals, and essay but only 10 relevant articles, electronic journals, and essay. The data were analyzed using qualitative descriptive analysis. The analysis result showed that cooperative learning type jigsaw model could improve student’s learning from the lowest 9,89% to the highest 85,56% and the mean was 46,09%